Problems Faced and Strategies Adopted by Farmers for Adapting to Climate Change in Xai-Xai District, Gaza Province, Mozambique - Filimone C; Humulane A; Fabião A; Dimande, B. (2015)
This research aims to:  Identify climate-related risks and challenges faced by Xai-Xai households (agriculture, livestock and forest resources);  Describe their current coping strategies and needs;  Recommend interventions that meet their needs and improve their livelihood resilience and adaptive capacity to climate variability.